Impact of pine plantation establishment on soil properties and fungal communities of natural forests in Zimbabwe. Issue 3 (16th November 2020) - Jimu, Luke; Nyakudya, Innocent W; Magogo, Charles; Mureva, Admore
Abstract : Globally, large expanses of land were cleared for the establishment of exotic pine and eucalypt tree plantations for commercial purposes. In Zimbabwe, these plantations resulted in the clearance of over 120 000 ha of native vegetation, especially miombo woodlands that are dominant in wetter regions of the country, to which these exotic species are mostly suited. To evaluate the effect of exotic pine plantations on soil physicochemical properties and fungal communities, we studied a second rotation pine plantation and adjacent miombo woodland. Soil nutrient concentration and pH were consistently higher ( p < 0.05) in the miombo woodland compared to pine plantation soils. Although both land uses were dominated by fungi belonging to Dikarya, pine plantation soil was dominated by Basidiomycota (69.1%) while miombo woodland soil was dominated by Ascomycota (66.1%). Basidiomycota in pine plantation soil was dominated by ectomycorrhizal associates of pine while Ascomycota in miombo woodland soil was dominated by saprophytic fungi.